Nursing science as a federally-recognized STEM degree: A call to action for the United States with global implications - Caitlin Dreisbach; Michelle L. Wright; Rae K. Walker; Ha Do Byon; Jessica Keim-Malpass (Elsevier, 2022)
Nursing science contributes to advancements in patient care, public health, and innovation within numerous scientific domains. Despite commonality with United States Department of Education definitions of a science, technology, engineering, and mathematics (STEM) educational programs, nursing continues to be excluded from Department of Homeland Security STEM classification. This exclusion prevents societal recognition of nursing as a science and limits attraction of clinicians and nurse scientists born outside of the United States due to omission from various federal visa provisions the Department of Homeland Security classification provides. We evaluated existing Department of Homeland Security STEM-classified educational programs and identified methodological and content congruency among STEM-classified programs and nursing. We provide clear evidence that nursing contributes impactful STEM research; and argue that inclusion is critical for advancement of the profession and the potential to mitigate the faculty shortage. Beyond evaluation of nursing as a STEM field, we offer a policy-focused solution for development and diversification of the nursing workforce.